Growth of liver allografts over time in pediatric transplant recipients. (15th January 2018) - Chaudhry, S. G.; Bentley‐Hibbert, S.; Stern, J.; Lobritto, S.; Martinez, M.; Vittorio, J.; Halazun, K. J.; Lee, H. T.; Emond, J.; Kato, T.; Samstein, B.; Griesemer, A.
Abstract: The liver's capacity to grow in response to metabolic need is well known. However, long‐term growth of liver allografts in pediatric recipients has not been characterized. A retrospective review of pediatric recipients at a single institution identified patients who had cross‐sectional imaging at 1, 5, and 10 years post‐transplant. Using volumetric calculations, liver allograft size was calculated and percent SLV were compared across the different time points; 18 patients ranging from 0.3 to 17.7 years old were identified that had imaging at 2 or more time points. Measured liver volumes increased by 59% after 5 years and 170% after 10 years. The measured liver volumes compared to calculated %SLV for these patients were 123 ± 37%, 97 ± 19%, and 118 ± 27% at 1, 5, and 10 years after transplant, respectively. Our data suggest that liver allografts in pediatric recipients increase along with overall growth, and reach SLVs for height and weight by 5 years post‐transplantation. Additionally, as pediatric recipients grow, the livers appear to maintain appropriate SLV.